The typology of female characters in the novels Intibаh and Days Gone By - Shukurova, Oysha (The Lingua Spectrum, 2025)
This article provides a comparative-typological analysis of the character system in Namık Kemal’s Intiboh and Abdulla Qodiriy’s O‘tkan kunlar. The study focuses on the structural role of characters in the development of the plot, their psychological and moral features, as well as their social and symbolic functions. Diloshub and Kumush are depicted as the spiritual cores of their respective novels, embodying fidelity, purity, and moral perfection, whereas Mohpaykar and Zaynab represent female characters whose lives are tragically destroyed by jealousy, envy, and inner conflicts. The research applies comparative literary criticism, literary psychology, and psychoanalytic approaches, including insights from Freud and Karen Horney, to interpret the destructive nature of jealousy. Findings reveal that in both novels, female characters serve as essential vehicles for reflecting moral values, social stereotypes, and the complexity of personal emotions within their societies. Ultimately, the study concludes that the portrayals of Diloshub, Kumush, Mohpaykar, and Zaynab contribute significantly to the understanding of female identity in Turkic novel traditions, illustrating the interplay between love, morality, and social constraints in the late 19th and early 20th centuries.